KONSENTRASI ANTI-HBs PADA KARYAWAN RUMAH SAKIT YANG TELAH MELAKUKAN VAKSINASI HEPATITIS B - Doni Setiawan (Masker Medika, 2023)
Introduction: Anti-HBs (Anti HepatitisLBLsurface) is an antibodyLto hepatitisLB that arises from the administration of the hepatitis B vaccine. Hospital employees areLat high riskLof contracting the hepatitis B virus, because they often have direct contact with patients, body fluids and medical equipment infected. ThisLstudy aims to determine the presence of hepatitis B antibodies in Ciamis Hospital employees after three years of vaccination. Method: ThisLstudy usedLa qualitativeLdescriptive methodLand was conducted in 2019. The population was 30 Ciamis Hospital employees who had received Hepatitis B vaccination three years previously. The instrument used was an examination using the ELISA (Enzyme-LinkedLImmunosorbent Assay) Lmethod. Results: LThe resultsLshowedLthat theLaverage levelLof Anti-HBs in employees was 42.46 mIU/mL which showed a positive result with an anti-HBs titer of 10 – 100 mIU/mL (normo-response). Conclusion: Thirty employees of Ciamis Hospital have good immunity, so hepatitis B antibodies can survive after three years of vaccination.